Tracking narrative change in the context of extremism and terrorism: adapting the Innovative Moments Coding System - Da Silva, R.; Fernández-Navarro, P.; Gonçalves, M. M.; Rosa, C.; Silva, J. (Aggression and Violent Behavior, 2019)
Existing models of deradicalisation, countering violent extremism (CVE), and counter-terrorism (CT) have lacked a clear theory of change, as well as robust empirical methodologies. This paper proposes an empirically-based systematic and transparent methodology – the Innovative Moments Coding System (IMCS) – which is empirically sensitive, ethically defensible, and can be of use in the context of research to inform practitioner contexts. Through a case study of former violent militants, we explore the adaptation and usage of this instrument to identify and track self-narrative change in the processes of engagement and disengagement, as well as radicalisation and deradicalisation in the context of violent extremism and terrorism. We illustrate how this methodology has the potential to bring benefits to the work of researchers involved in producing guidelines for disengagement, deradicalisation or risk-reduction interventions.